The hydrational effect of alkali metal and halide ions on the Rh-anti-Rh system - Good, W. (1971)
An examination has been made of the action of alkali metal and halide ions on the Rh-anti-Rh system. Under conditions in which differences due to electrostatic effects are minimal, there is appreciable variation in the experimental response measured by the Race score. This variation is attributed to hydrational effects of the ions and it is noted that the erythrocyte permeability of halide ions complicates their behaviour. It is suggested that ionic hydration is an important factor governing the magnitude of the entropy change that accompanies Rh-anti-Rh combination in the first stage reaction.